RELATIONS WITH THE KNOWLEDGE AND ATTITUDE STUDENT PERCEPTION OF TRANSMISSION HIV / AIDS IN SMA N 4 JAMBI - Eko Eko; Retty Octi Syafrini (Jurnal Akademika Baiturrahim Jambi, 2016)
Background : Malignancy and the dangers of AIDS, it is terrible especially for causing a death sentence, to anyone who has been the victim. Remarkably AIDS is also a disease lethal side labeled executive, expensive to maintain. Concern on nursing care of HIV / AIDS is highly dependent on knowledge and attitudes. This research is a quantitative research with cross sectional design that aims to determine the relationship of knowledge, attitude and perceptions of students about the transmission of HIV / AIDS in SMA public 4 Jambi city. Methods : The study was conducted on 12-14 March 2016 with a sample of 80 respondents . The data were obtained using a questionnaire, analyzed by univariate and bivariate, looking for relationships using the chi-square test. Results : The study was conducted on 12-14 March 2016 with a sample of 80 respondents . The data were obtained using a questionnaire, analyzed by univariate and bivariate, looking for relationships using the chi-square test. Conclusion : It is hoped that the school can remind their students about the devastating impact of HIV / AIDS through the media, as well as the provision of additional activities either on its core activities and extracurricular activities that are physical and spiritual religious.